2016
DOI: 10.19082/3228
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Perception and Preference of Drinking Water Sources

Abstract: IntroductionUnderstanding consumer perception of drinking water can contribute to improvements in water management and consumer satisfaction. The aim of this study was to assess the consumer perception of tap water quality and other drinking water sources in Gonabad as a small semiarid city.MethodsThis study was performed in autumn and winter 2013. For collection data a researcher-made a questionnaire consisting of nine questions, based on demographic information prepared. Questions were asked for participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 13 publications
1
8
1
5
Order By: Relevance
“…Between 83 and 90% across the four categories rejected the water. This is contrary to the results of Sajjadi et al (2016), who found in a survey about water quality perception in Iran that volunteers' acceptance differed greatly across the societal strata. There appears to be no correlation (for α = 5%) between the HDI of the neighborhood that the volunteer lives in and whether the tap water is rejected or accepted.…”
Section: Reasons For Acceptance/rejection Of Tap Watercontrasting
confidence: 99%
“…Between 83 and 90% across the four categories rejected the water. This is contrary to the results of Sajjadi et al (2016), who found in a survey about water quality perception in Iran that volunteers' acceptance differed greatly across the societal strata. There appears to be no correlation (for α = 5%) between the HDI of the neighborhood that the volunteer lives in and whether the tap water is rejected or accepted.…”
Section: Reasons For Acceptance/rejection Of Tap Watercontrasting
confidence: 99%
“…Karyawati kantoran wanita dan keluarga miskin merasa puas dengan kualitas air minum keran, sehingga mereka lebih memilih penggunaan air keran sebagai sumber air minum dibanding air kemasan. (Sajjadi et al, 2016). Penelitian di banyak negara tersebut di atas secara garis besar menemukan alasan keamanan kualitas, keamanan untuk kesehatan dan pertimbangan ekonomi sebagai faktor yang melatarbelakangi penggunaan air kemasan sebagai sumber air minum rumah tangga.…”
Section: Pembahasanunclassified
“…Ahora se analiza otra variable que proporciona información del consumo de agua, que no proviene de la red pública (figura 3). La adquisición de bidones de agua potable, estaría relacionada con la insatisfacción y/o desconfianza del usuario con la calidad del agua de la red de distribución (Doria, 2006;Ali Sajjadi et al, 2015). Por esta razón se analiza los consumos per cápita de agua en bidones en los estratos socioeconómicos de las 11 ciudades.…”
Section: Ingecap Deficiente Regularunclassified
“…Las preferencias de consumo de agua potable o embotellada varían de acuerdo a características demográficas y socio económicas (Ali Sajjadi, Alipour, Matlabi & Biglari, 2015;Morote Seguido, 2017). La información obtenida en las investigaciones realizadas en las poblaciones Ecuatorianas entre el 2013 y 2015 muestran los patrones de los consumos de agua potable en rangos de poblaciones bien definidos (Arellano, Bayas, Meneses & Castillo, 2018).…”
Section: Introductionunclassified
See 1 more Smart Citation